MODEL APLIKASI FIKIH MUAMALAH PADA FORMULASI HYBRID CONTRACT - Murtadho, Ali (Al-Ahkam, 2013)
Modern literatures of fiqh muâ€™Ämalah talk alot about various contract formulation with capability of maximizing profit in shariah finance industry. This new contract modification is the synthesis among existing contracts which is formulated in such a way to be an integrated contract. This formulation is known as a hybrid contract or multicontract (al-'uqÅ«d al-murakkabah). Some of them are, bay' bi thaman 'Äjil, IjÄrah muntahiyah bi â€™l-tamlÄ«k dan mushÄrakah mutanÄqiá¹£ah. This study intends to further describe models of hybrid contract, and explore the shari'ah principles in modern financial institutions. This study found a potential shift from the ideal values of the spirit of shari'ah into the spirit of competition based shari'ah formally.